2002
DOI: 10.1002/sia.1339
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of CaSi2 on Si(111)

Abstract: Thin Ca films were evaporated on Si(111) under ultrahigh vacuum conditions and annealed in the temperature range 200-650• C. The interdiffusion of Ca and Si was examined by ex situ Auger depth profiling. In situ monitoring of the Si 2p core-level shift by x-ray photoelectron spectroscopy was employed to study the silicide formation process. The formation temperature of CaSi 2 films on Si(111) was found to be ∼350 • C. Epitaxial growth takes place at ≥400 • C. The morphology of the films, observed by atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…In contrast, the x-ray photon spectroscopy ͑XPS͒ results for calcium silicides, 26,27,[29][30][31] and in particular CaSi, are ambiguous because of the surface sensitivity of this method. These results have been obtained mainly for the silicide films on Si surfaces with a Ca deposition.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, the x-ray photon spectroscopy ͑XPS͒ results for calcium silicides, 26,27,[29][30][31] and in particular CaSi, are ambiguous because of the surface sensitivity of this method. These results have been obtained mainly for the silicide films on Si surfaces with a Ca deposition.…”
Section: Resultsmentioning
confidence: 80%
“…At the initial stage of the film's growth, the Si 2p photoelectron spectra showed a larger negative chemical shift ͑1.1-1.45 eV͒, while a smaller negative chemical shift ͑0.3-0.4 eV͒ was observed after the CaSi 2 films formed. 26,27 Schöpke et al 27 concluded that a larger chemical shift arose from the formation of the Ca-rich silicides, such as Ca 2 Si and CaSi. The local structure of the Si atoms in CaSi, however, resembles that of CaSi 2 rather than Ca 2 Si, where the nearest-neighbor atoms of Si are Ca atoms, because the nearest-neighbor atom of Si in CaSi 2 is not Ca but Si.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CaSi 2 epitaxial films were grown on Si substrates by solid-phase epitaxy (SPE) [10][11][12][13] and reactive deposition epitaxy (RDE). [9,[14][15] The epitaxial relationship is CaSi 2 (0001)/Si{111} [14] with the lowest lattice mismatch of 0.4 %.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, methods for fabricating epitaxial films of calcium silicides on silicon are limited to the evaporation of calcium metal onto Si wafers followed by an anneal to produce CaSi 2 . [10][11][12] In addition, CaSi 2 and CaSi melts, prepared by heating of Ca and Si in stoichiometric proportion, exhibit superconducting behavior at high pressures, 13,14 and show potential for reversible hydrogen storage, 15 respectively.…”
Section: Introductionmentioning
confidence: 99%